Environmental Engineering (Laboratory) - Ngadiman, Norhayati; Hamid, Nor Baizura; Abdullah, Noorul Hudai; Sahat, Suhaila; Abdul Kadir, Muhammad Azraie (Penerbit UTHM, 2021)
This module will give the students an understanding of the Environmental Engineering (Laboratory) for the course DAC 12203 offered by the Centre of Diploma Studies (CeDS), Universiti Tun Hussein Onn Malaysia (UTHM).